Encontro de Aedes (Stegomyia) albopictus (Skuse) em Bromeliaceae na periferia de São Paulo, SP, Brasil The Aedes (Stegomyia) albopictus (Skuse) breeding in Bromeliaceae on the outskirts of an urban area of Southeastern Brazil - Delsio Natal; Paulo R. Urbinatti; Carmen B. Taipe-Lagos; Walter Cereti-Júnior; Anita T. B. Diederichsen; Roberta G. Souza; Renato P. Souza (Universidade de São Paulo, 1997)
Foram coletadas larvas de Aedes albopictus em uma planta da família Bromeliaceae, na periferia da cidade de São Paulo, SP, Brasil. Esse encontro abre perspectivas de estudo para avaliação do potencial desse vegetal como criadouro desse mosquito no País. Larvae of Aedes albopictus from a plant of the Bromeliaceae family on the outskirts of S. Paulo, SP, Brazil, were collected. This occurrence sheds new light on the attempt to determine the potential of this plants as a breeding site for this mosquito in Brazil.